Use of Autonomy-Supportive and Controlling Behaviors - Tucker Readdy; Johannes Raabe (University of Kansas Libraries, 2016)
Grounded in self-determination theory (Deci & Ryan, 1985, 2000), the coachathlete relationship model (Mageau & Vallerand, 2003) suggests that coaches can positively affect athletes' basic psychological needs satisfaction and motivation through autonomy-supporting behavior. Yet, little research has explored coaches' objective use of autonomy support or the personal and contextual demands associated with such interactions. The current study used a mixed-methods design to describe coaches' utilization, perceived benefits of, and challenges to the provision of autonomy support during an NCAA football season. Participants were nine assistant coaches at a Division I university. Each coach was live-coded at one practice each week for the duration of the 12-game schedule. At midseason, participants received a report of the percentage of interactions in teaching, organization, cheering, autonomy support, and controlling behaviors, as well as recommendations for improvement. Coach-level RM-ANOVA results demonstrated a variety in the number and magnitude of statistically significant changes in four of the five behavior categories; effect sizes ranged from small to large. Postseason interviews suggested coaches were attuned to the results and suggestions of the report, but that both personal and social influences (e.g., knowledge of SDT, competition with other coaches) as well as contextual factors (e.g., time constraints of practice, competition results) were also important in influencing behavior change. Thus, autonomy support is a viable and valuable pursuit in the context of collegiate athletics, but further development of practical, effective strategies is needed.